2016
DOI: 10.7763/ijiet.2016.v6.741
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Design of Management Senior Project for Engineering Students

Abstract: Abstract-The senior project course for engineering students has a vital role in complementing the "learn by doing" education engineering students in any university. The senior project course is, usually, a two semester course. This short time frame, poses challenges for both students and faculty. Students have to achieve the outcomes of the project to a certain extent and the faculty has to manage, follow up and evaluate efficiently the work of their students individually and by group. One common problem in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The study showed that the least important responsibility of a supervisor is to tell the students what to do or how to solve a problem. Another example is to deal with the "free-rider" situation and to fairly measure the student's progress [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that the least important responsibility of a supervisor is to tell the students what to do or how to solve a problem. Another example is to deal with the "free-rider" situation and to fairly measure the student's progress [5,6].…”
Section: Introductionmentioning
confidence: 99%